Examining the Application and Use of the Baby-Friendly Initiative within Rural and Urban Health Facilities in Canada among Indigenous Mothers - Bacciaglia, Meagan (University of Waterloo, 2023)
Background: To prevent infant mortality and morbidity, WHO and UNICEF established the Baby-Friendly Hospital Initiative (BFHI) to support breastfeeding initiation and duration by improving the quality of care provided in health facilities globally. Indigenous communities across the world report lower breastfeeding rates compared to non-Indigenous populations. There is very limited research surrounding the implementation of the BFI (Baby-Friendly Initiative) within Canada to support Indigenous women. Research Questions: This study sought to answer: 1) How is the BFI implemented and utilized among health facilities that service Indigenous women in Canada? 2) What is the availability and utilization of the BFI among Indigenous women? 3) Are there differences in the uptake of the BFI between rural and urban health facilities? Methods: Qualitative methodologies and methods, including semi-structured interviews, case study research, and document analysis were implemented to examine the experiences of policymakers, health service providers, and health organizations. Seven participants were recruited from international and national health organizations, bodies of the Canadian government, and Canadian health facilities. Inuvik Regional Hospital and Grey Nuns Hospital were reviewed as the case studies through using documentary analysis. The Interactive Theory of Breastfeeding was used to inform the study design and frame the results. Results: A conceptual model utilizing the social-ecological framework was created to expand the Interactive Theory of Breastfeeding, and contextualize the participant experiences of implementing the BFI, decisions to breastfeed, and the cultural appropriateness of the BFI for Indigenous women. Through the adapted model, a unique contribution includes the incorporation of Indigenous traditions and context. Previous models have not specifically examined policy and environmental influences relating to breastfeeding and Indigenous women within Canada. Conclusion: There is an opportunity for the ...